Cephalic duodenopacreatectomy in the treatment of a bleeding duodenal ulcer in pancreas transplants - Pires, Izadora Santos Simões; Siqueira, Rodrigo Morais de; Kroth, Leonardo V.; Hartmann, Marcelo; Falavigna, Manlio; Traessel, Moacir Alexandre; Carvalhal, Eduardo Franco; d’Avila, Domingos; Saitovitch, David; Gullo Neto, Salvador (Brazilian Journal of Transplantation, 2009)
Pancreas transplantation is currently the only known therapy which restores glycemic metabolism in type 1 diabetic patients. The most prevalent indication is in association with kidney transplantation in patients with type 1 Diabetes Mellitus (DM1) and nephropathy, who are under dialytic treatment. It can be detached among the complications of simultaneous pancreas and kidney transplantation (SPK): sur- gical re-interventions, especially those resulting from complications of bladder exocrine pancreatic drainage, with considerable morbidity and mortality. In this report, we present a clinical case of a 31 years-old Caucasian male patient with DM1 since he was 12 years-old, and on hemodialysis for two years, until he was submitted to a SPK two years ago. He then developed massive hematuria due to a bleeding duodenal graft ulcer. The use of the segmental pancreatic technique with pancreaticocystostomy for exocrine pancreatic drainage allowed the maintenance of the graft and the euglycemic state of the patient free of exogenous insulin.